Mobbing w Kościele? Analiza teoretyczna i implikacje do stworzenia systemu wewnątrzkościelnej prewencji antymobbingowej w Polsce - Chrostowski, Mariusz (Poznańskie Studia Teologiczne, 2022)
Mobbing can be described as an important social problem, but also an urgent theological and pastoral issue, which in the Church is a close combination of spirituality and power, conducive to silencing both the person being intimidated and witnesses. Also, taking into account the effects of mobbing in ecclesial circles, it must be stated that they leave much more serious consequences than those faced by people employed in other organizations as they lead to strong internal tensions and suffering not only psychological, but above all spiritual. In this context, the aim of this article is a theoretical analysis of the phenomenon of mobbing, i.e. outlining its main characteristics and manifestations (also of a spiritual and religious nature) in the Church and its subordinate institutions. It is also to develop a catalogue of practical implications that could form the basis for creating a future-oriented and, possibly effective, system of intra-church anti-mobbing prevention.